Preparation of extracts from tropical plants for· electrophoresis - an analysis of methodology - Gan, Yik Yuen (Universiti Pertanian Malaysia, 1985)
Electrophoretic analysis of enzymes from tropical plants can be very diffie-ult due to the presence of high concentrations of phenolics in plant tissues. It is believed that these high tannin levels may serve to protect plants from the numerous insect predators present in the tropics. Different methods of extraction of enzymes prior to electrophoresis are suggested. A number of factors which make plant proteins practically unstable and difficult to work with are also mentioned. The occurrence of tannins in plants and the reactions of these phenolic compounds with proteins and enzymes are discussed. Techniques for the extraction of enzymes from tannin-rich plants should involve the removal of phenolic substrates, the inhibition of O-dlfthenol-oxidase activity or the removal of quinones formed from oxidation by reducing the quinones back to the O-dlfthenol. Chemicals added into the extracting medium to overcome the problem of interference by tannins include polymers, copper chelating agents, thiols, ascorbate, metabisulphite, dithionite and b01!ine serum albumin.